Paciente de sexo femenino de 69 años de edad con insuficiencia renal crónica - Pisco Rodríguez, Ariana Isabel (2018)
The case report presents a 69-year-old patient with chronic renal failure. Chronic kidney failure is about your kidneys being affected and can not filter the blood as it should and this causes the accumulation of waste in your body causes changes in your health. In our care plans that we chose our patient we were able to restore it thermodynamically thanks to our interventions. In the process of nursing care, our priority was to control the electrolytes and fluid management of a patient with Chronic Renal Insufficiency. The treatment that is carried out is hemodialysis that this is about purifying the blood of the organism since it accumulates waste.